Handbook of energy audits, eighth edition - Thumann, Albert; Niehus, Terry; Younger, William J. ([S.l.] : CRC Press, 2009)
This bestselling handbook is the most comprehensive and practical reference available on energy auditing in buildings and industry. This latest edition includes revisions throughout covering ASHRAE Level 1 and 2 energy audits, as well as a new chapter on water conservation. Topics include energy assessment and computer software that will guide you in planning and carrying out a thorough and accurate energy audit for any type of facility, including electrical, mechanical, and building systems analysis. Clear, easy-to-follow instructions guide you through accounting procedures, rate of return, and life cycle cost analysis. Also covered is information on understanding your utility bill and using that knowledge to trim your energy costs. Loaded with forms, checklists and handy working aids, this book is must reading for anyone responsible for conducting or overseeing a facility energy audit.
Keywords: Energy auditing; Energy conservation; Energy consumption